Cross-Cultural Correlates of the Ownership of Private Property: A Look from Another Data Base - Rudmin, Floyd Webster (Anthropologica, 2022)
Swanson's (1966) data base of 39 variables coded on 50 cultures was re-examined for cross-cultural correlates of the private ownership of property. Reliability comparisons were made with Murdock's (1967) Ethnographic Atlas. Eliminated were one of Swanson's cultures because of duplicate sampling of a culture cluster, and seven variables because of doubtful reliability. A conservative statistical analysis (p < .0003) showed the social institution of private ownership to be a positive correlate of (1) social classes, (2) agriculture in grain, (3) supernatural sanctions for morality, (4) primogeniture, (5) active ancestral spirits, (6) sovereign organization, (7) size of population, and a negative correlate of (8) collecting and gathering, (9) outgroup intimacy and (10) hunting. Theories that private property is a function of patriarchy were not supported, nor were arguments that property regimes are advanced by exogamy and other intimate interactions with alien people